PROMOTING CRITICAL THINKING THROUGH ONLINE EDUCATION COMMUNITY TOOL - Rina Sari; Djoko Susanto (PARADIGM: Journal of Language and Literary Studies, 2020)
This study aims at figuring out whether online community education tool can beused as the platform fostering critical thinking skills of the users. Enhancing criticalthinking involves increasing the skill to pursue solutions to nontrivial problems thatcan be done though asking questions, making inference, and communicating ideas.These skills are also required in English language interaction especially during theera of distant learning. In English language learning at Madrasah, the interactionstrategies commonly used cover the classical method such as lecturing, question andanswer and giving assignments. The use of social media helpful for languagelearning is not familiar. This study employs action research design collaboratingwith some High school teachers in Malang, Indonesia. It is significant for shapingthe learners’ critical thinking through the use of social media for English languagelearning method at madrasah level. It is also a significant step to develop criticalthinking.